KONSEP TUHAN DALAM AGAMA KRISTEN (KAJIAN BUKU SEJARAH TUHAN KAREN ARMSTRONG) - Juwaini Juwaini (Prodi Studi Agama-Agama, 2021)
Talking about God has always been a topic of conversation among theologians. Karen Armstrong as a theologian tries to explain the existence of God. Her book entitled The History of God, Karen Armstrong describes in detail the existence of God in the history of human life. The book tells about Karen Armstrong's hesitation in finding the essence of the Trinity in the concept of Christian divinity. Karen Armstrong went through several phases in her skepticism to reach the essence of God in her faith. This paper will discuss Karen Armstrong's view of the Concept of God in Christian Religion using descriptive analysis of the book History of God. The results of the study show that in Christianity the concept of divinity exists in the Trinity, namely God the Father, God the Son and the Holy Spirit. Where Jesus Christ is considered as God because it is believed that Jesus is the Word who became human. The strengths and weaknesses of the Trinity in Christianity that are not understood by everyone. The history book about God examines the history of human perceptions and experiences of God from the time of Prophet Abraham to the present. Karen Armstrong explains in detail the three monotheistic religions, namely Judaism, Christianity and Islam. The book also features Buddhist, Hindu and Confucian traditions. For Karen Armstrong Religion is not about believing in something. Religion is a matter of morals, behaving in ways that change oneself, bringing oneself closer to the holy and sacred.